A Shift in IR Approach after Ukraine War: Remilitarization of Europe, an Interpretation Through the Realist Lens - Shysti BUSHATI; Mirela ALHASANI (DUBALI) (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2023)
In the research my aim will be to give an explanation on the response and actions of the European countries during the Ukraine war through a realist perspective. The Ukraine war is potentially the new case that has left space for interpretation on the realist interpretation as well as possibly giving room for arguments in criticism of the liberal or neoliberal thinking. Priority will be given to the time frames surrounding the annexation of Crimea and up until the Ukraine War. The conflict's origins and its effects will then be largely interpreted from a realism standpoint. The process of analyzing will be as mentioned priorly in explaining the occurrences during the Ukrainian revolution and the potential clash of interest between the major power or actors (USA, EU, Russia). Further explanation will be given in the approaches of the European country’s response to the threat of the Ukraine war, in which the majority of countries choose to increase their military capabilities. It must be noted in my findings that some of the diplomatic elements despite their presence throughout the conflict, the outcomes of them were not very successive, leaving again most of the countries to choose further rearmament rather than diplomatic language. The highlighted aspect in this case is the increase of importance in military power and military alliances as a form of balancing power and maintaining security as well as deterring potential aggression.